Analisis Pembatalan Keputusan tentang Penetapan Tanah Terlantar yang Berasal dari Hak Guna Bangunan - Theresia Rizka Ully Situmorang; Muhammad Yamin dan Rudy Haposan Siahaan (CV Rewang Rencang, 2025)
Abandoned land is a serious problem in land management in Indonesia that requires appropriate supervision and control mechanisms. This research analyzes the annulment of decisions on the determination of abandoned land originating from Building Use Rights through a case study of Decision Number 150/G/2019/PTUN-JKT. The research method uses a normative juridical approach with court decision analysis. The research results show that the annulment of the decision was caused by violations of administrative procedures and administrative law principles, particularly in the identification, evaluation, and warning stages. This research concludes the need to apply the principle of prudence and good governance in determining abandoned land to ensure legal certainty and protection of rights.